Effect of different clay additions to concrete on its ultrasonic acoustic parameters and compressive strength - Wenxiang Wu; Shunchao Chen; Yong Wu; Xiangyang Zhang; Debiao Kong; Jifeng Wen (Scientific Reports)
Abstract Due to various factors, the concrete may contain mud, a condition that can lead to a decrease in strength and changes in the ultrasonic acoustic parameters of the concrete. In order to study the effect of concrete mud content ( $$\:{γ\:}_{Mc}$$ ) on ultrasonic acoustic parameters and compressive strength, this paper firstly derived the relationship equations between concrete mud content and acoustic parameters and compressive strength. Subsequently, the acoustic parameters and compressive strength were tested for concrete specimens with different mud contents cast on site. Finally, the effects of concrete mud content on wave velocity, sound time, amplitude, frequency and strength were analyzed according to the measured acoustic parameters, and the relational equations of mud content on acoustic parameters were verified, which provided a reference for evaluating the defective degree of concrete mud content. The main conclusions are: According to sound field theory, the higher the mud content of concrete, the lower its strength, the higher the sound time value, the lower the sound velocity value, and the smaller the amplitude value. The measured data shows that as the age of concrete containing mud increases, its sound velocity value increases, the sound duration value decreases, the amplitude changes are dispersed, and the frequency value increases. Specifically, with the increase of concrete age and when $$\:{γ\:}_{Mc}$$ is between 0 and 10%, the changes in concrete sound velocity and sound time are minimal; With the increase of concrete age and when $$\:{\:γ\:}_{Mc}$$ exceeds 20%, the frequency value significantly increases; The changes in amplitude values are similar during the age of concrete from 7 to 28 days. The measured parameters indicate that an increase in the mud content of concrete will lead to a decrease in its compressive strength, a decrease in sound velocity, an increase in sound duration, a decrease in amplitude, and a decrease in frequency. This law is highly consistent with theoretical deductions. Specifically, as $$\:{γ\:}_{Mc}$$ increases, there is a non-linear relationship between compressive strength and $$\:{γ\:}_{Mc}$$ (R²=0.97); When $$\:{γ\:}_{Mc}$$ is greater than 10%, the sound velocity and sound time values change significantly, and both show linear and nonlinear relationships with the mud content; As $$\:{γ\:}_{Mc}$$ increases, the amplitude also exhibits a nonlinear relationship with $$\:{γ\:}_{Mc}$$ (R²=0.91);When $$\:{γ\:}_{Mc}$$ is greater than 20%, the frequency value changes significantly and shows a linear relationship with $$\:{γ\:}_{Mc}$$ (R²=0.95).In addition, concrete with higher mud content has a longer first wave period, larger waveform spacing, and faster signal attenuation.